Высшее образование и производство: проблемы и пути их решения - Каримов, Х.Н; Имамов, Э.З; Имамов, А.Э; Исмайлов, К.А; Аскаров, М.А (SCIENCE and SOCIETY, 2024)
The successful implementation of the proposed approach to the training of highly qualified personnel for modern production is possible with the operational and mutually interested partnership activities of the university and production. Especially рartnership activity is important between the heads of an educational institution and an enterprise, as well as relevant line ministries and departments.
Keywords: integrated educational process; improvement; specialized branch; academic activity; personnel consumers; curriculum; specialty disciplines